In Vitro Propagation of Carrot (Daucus Carota) L. - Pant, B; Manandhar, S (Scientific World, 2010)
In vitro method for rapid propagation of Daucus carota L. was developed. Root, stem, leaf and nodal explants were cultured on MS medium supplemented with different concentration and combinations of hormones. Multiple shoot were induced from the nodal explant of D. carota by culturing them in MS medium supplemented with 0.5 mg/l of 6-benzylaminopurine (BAP). Differentiation of shoot initiated after one week of culture, and after eight weeks of primary culture, an average of six plantlets were developed from a single shoot. The nodal explant also induced same number of multiple shoot in MS medium supplemented with 2 mg/l of BAP and 1 mg/l of α-nephthalene acetic acid (NAA). The shoots when sub-cultured in the medium supplemented with 1 mg/l NAA produced roots after five weeks of sub-culture. Root and leaf explants induced roots and callus when cultured on MS medium with NAA at the rate of 1 mg/l and 2 mg/ l. Similarly, stem explants also induced roots and callus in the same concentration of hormones whereas few multiple shoot were induced when cultured on MS supplemented with 2 mg/l of BAP and 1 mg/l of NAA. This result suggests that this methodology can be applied for the rapid and mass propagation of this species. Key words: In vitro; Propagation; MS medium; Explant; Culture. DOI: 10.3126/sw.v5i5.2656 Scientific World, Vol. 5, No. 5, July 2007 51-53